The malfunction of public authorities in the spatial planning system - Foryś, Iwona; Nowak, Maciej (Publishing House of Wroclaw University of Economics and Business, 2022)
The aim of the paper was to adapt the concept of the malfunction of public authorities to the spatial management system and to propose methods on the basis of which it can be verified. The paper contains a theoretical review, in which the context of the malfunction of public authorities in the spatial management system is presented, as well as an indication of the plane of malfunction verification from a formal and legal perspective. This concerns the judicial decisions of the Supreme Administrative Court relating to key planning tools, namely studies of the conditions and directions of spatial development and local spatial development plans. A definition of the malfunction of public authorities and its measurement were proposed, along with binomial models for analysing this phenomenon.
Argumenta Oeconomica, 2022, Nr 1 (48), s. 265-289
Keywords: institutional economics; system malfunction; spatial planning; logit models